The Day-of-the-week Effect in the Hang Seng Index - Chia, Ricky Chee-Jiun; Liew, Venus Khim-Sen; Syed Azizi Wafa, Syed Khalid Wafa (EconBiz, 2015)
This study finds the existence of Friday effect in the return of Hang Seng Index. This finding implies that the Hong Kong Stock market is inefficient with respect to price information. Besides, the Hang Seng Index returns are predictable and hence profitable trading strategies can be developed. Thus, investors could use the day-of-the-week effect information when investing in the Hong Kong stock market.